Appropriate placement of vapour recompression in ultra-low energy industrial milk evaporation systems using Pinch Analysis. (1st December 2016) - Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R.W.; Neale, James R.
Abstract: This study focuses on applying Pinch Analysis to an industrial milk evaporator case study to quantify the potential energy savings. Modern milk evaporators are typically integrated using both mechanical and thermal vapour recompression technologies as the primary means for attaining a high level of energy efficiency. A significant step change in energy efficiency for milk evaporators is achieved in this study by appropriate placement of vapour recompression in a new improved two-effect milk evaporation system design. The Grand Composite Curve helps identify areas for process modifications and placements of vapour recompression that result in energy reduction. In particular, the innovative placement of Mechanical Vapour Recompression in the system unlocks significant energy, energy cost, and emissions savings. The new design requires 78% less steam (6397 kW) at the expense of 16% (364 kWele ) more electricity use. The estimated cost savings associated with the improved design is $942, 601/y and the emissions reduction is 3416 t CO2 -e/y. Further energy efficiency improvements and cost savings of $1, 411, 844/y are gained through improved Total Site Heat Integration through recovery of waste heat from the dryer exhaust air and boiler return condensate streams. Highlights: The industrial milk evaporation system design problem is investigated. Pinch Analysis and process modelling are successfully sequentially applied. Appropriate placement of vapour recompression unlocks large energy savings. A proposed evaporation system design uses 78% less steam, 16% more electricity. The energy cost savings potential across the Total Site is $2.35 M/y.